Leisure participation and satisfaction for healthy lifestyles - Monte, Rowena N. (2008)
Leisure activity participation is particularly important during adolescence because it provides them opportunities to discover and develop their interest, exercise autonomy and define their identity. Through engagement in leisure activities, they would acquire additional knowledge of the socio-cultural environment, practice social and cooperative skills, experience intellectual or physical attainments and deal with a variety of peer and community roles. A modified questionnaire of Ragheb and Beard's Leisure Satisfaction Scale (LSS) was employed to identify the determinants in participation in leisure activities and determine the underlying dimensions that account for leisure satisfaction of tertiary students in the University of the Philippines Los Banos. Findings reveal that the nature of the activities participated in by tertiary students are those that are relaxing and for good health. Their leisure satisfaction is best described in four dimensions, namely: social-educational, physiological, physical-environmental and relaxational. The level of leisure satisfaction is generally similar in all the clusters of determining factors. The result implies that these students nurture not only their physical health but their emotional health as well. There is always a need to have a wholesome leisure activity to maintain a healthy lifestyle and hence, a healthy environment, man being a part of the environment.
Keywords: Leisure; Recreation for college students; Environmental health